2015
DOI: 10.3390/jfb6030833
|View full text |Cite
|
Sign up to set email alerts
|

Grafts for Ridge Preservation

Abstract: Alveolar ridge bone resorption is a biologic phenomenon that occurs following tooth extraction and cannot be prevented. This paper reviews the vertical and horizontal ridge dimensional changes that are associated with tooth extraction. It also provides an overview of the advantages of ridge preservation as well as grafting materials. A Medline search among English language papers was performed in March 2015 using alveolar ridge preservation, ridge augmentation, and various graft types as search terms. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 67 publications
1
68
0
5
Order By: Relevance
“…Both groups showed a high percentage of residual bone substitute. This result was correlated with various studies conducted on bovine bone showed retention of graft up to 3 years 16,31,53 . Bovine bone seemed to act as semipermanent grafting material.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both groups showed a high percentage of residual bone substitute. This result was correlated with various studies conducted on bovine bone showed retention of graft up to 3 years 16,31,53 . Bovine bone seemed to act as semipermanent grafting material.…”
Section: Discussionsupporting
confidence: 88%
“…It may be considered an aggressive method to harvest autogenous bone for small defects as extraction socket. Furthermore, bone substitutes showed higher volumetric stability compared to autogenous bone 5,[31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…A further improvement is the customization of allogeneic bone blocks with a precise defect fit, which is especially of added value for complex bone augmentations, as the space between residual bone and bone graft can be condensed to a minimum. Thereby, the physical contact between graft and recipient site is enhanced, thus allowing optimal trophic support and revascularization of the allograft through integration/replacement (creeping substitution) at the recipient site 20,21 . Additionally, this uninterrupted connection to the adjacent bone tissue enables a rapid bony integration.…”
Section: Discussionmentioning
confidence: 99%
“…Bone graft materials have been used clinically in attempts to regenerate periodontal defects to original levels, involving reconstruction of alveolar bone, periodontal ligament, and cementum. To obtain optimal bone regeneration, all grafts require an adequate blood supply, a form of mechanical support, and osteogenic cells derived from the host, graft material, or both 33 . Graft resorption, called biodegradation, should take place at a time appropriate to activation of new bone formation 34 .…”
Section: Discussionmentioning
confidence: 99%